Enforcement of Human Rights through Criminal Law Against Environmental Destruction Due to Batik Industry Activities - Rayhan Fiqi Fansuri; Juan Matheus (Universitas Negeri Semarang, 2022)
Water as one of the basic needs must be maintained both in quality and quantity. However, the occurrence of pollution in watersheds due to the influence of wastewater quality that exceeds the quality standard of wastewater can affect the carrying capacity of the environment around the river which has an impact on the violation of community rights to a good and healthy environment. One example of river water pollution occurred in the Bengawan Solo River due to the activities of the batik cloth industry in the Laweyan area. The pollution of the Bengawan Solo River is due to the lack of strict legal rules governing violations of waste water quality standards so that river water pollution is rampant and of course violates human rights for a clean and healthy environment. Currently, the article that regulates the violation of waste water quality standards is regulated in Article 100 paragraphs (1) and (2) of the Law on Environmental Protection and Management. To suppress the occurrence of river water pollution which is a violation of human rights, strict rules are needed by applying the principle of primum remedium. The research method used in this paper is a normative juridical method by examining secondary data with a statutory approach, a case approach, a conceptual approach, and a historical approach. For this reason, it is necessary to apply the principle of primum remedium to prevent river water pollution so that human rights for a good and healthy environment and obtain clean water can be enforced.